PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, KOMUNIKASI, DAN SARANA PRASARANA TERHADAP KESIAPAN PEMERINTAH DAERAH DALAM PENERAPAN “PP NOMOR 12 TAHUN 2019” - sri mulya saputri; nur azlina; rofika rofika (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2021)
This study aims to determine the effect of the competence of human resources, communication and infrastructure on the readiness of local governments in implementing “PP No. 12 of 2019” in the local government of Rokan Hulu district. The population and sample in this study amounted to 45 OPD or 180 respondents. Sampling technique used in this study is saturated sampling, and the data analysis method used is multiple regression analysis using SPSS version 26. The results of this study indicate that the competence of human resources, communication and infrastructure has a significant effect on the readiness of local governments in implementing Government Regulation “No. 12 of 2019”.